Actitudes hacia la investigación científica y su relación con el rendimiento académico de los estudiantes en el semestre académico 2007-I, en la asignatura de Tesis II de la Facultad de Educación y Humanidades – Rioja de la Universidad Nacional de San Martín. - Góngora Silva, Liliana (2009)
The increasing importance that the science has acquired in our society and the paper(role) increasingly relevant that the scientist recovers(plays) in the human occupation, to solve the problems in a society, is a need of the universities to form(train) investigators(researchers) in each of the areas of the science. The investigators'(researcher) formation(training) is directly linked by the education. In the Faculty(Power) of Education Humanities, located in the province of Rioja, of the National University of St Martin, have the opportunity to develop in the study plan of the professional career(race), subjects orientated to the investigation(research) since(as,like) they are: Methodology of the Scientific lnvestigation(Research), Scientific lnvestigation(Research) in Education, Thesis I, Thesis the llnd and thesis the lllrd. The curriculum of the Faculty(Power) of Education and Humanities it(he) is orientated to that his(her,your) gone away ones(graduated ones) are capable of 'realizing scie11tific investigation(research). it is important to indicate that a separation exists between(among) the systematizing of the experiences of learning and the results that are waited, on to having executed the above mentioned experiences of learning. Therefore, it is necessary to realize an investigation(research) that is orientated to relate the attitudes towards the scientific investigation(research) and the academic performance(yield).From the perspective, the aim(lens) of the investigation(research) is to determine the relation that exists between(among) the attitudes towards the scientific investigation(research) and the academic performance(yield) of the students in the academic semester 2007-I, in the subject of Thesis the lllrd of the Faculty(Power) of Education and Humanidades-Rioja of San's Martin National University-Tarapoto; hipotetizando that the attitudes towards the scientific investigation(research) relates directly proportionally to the academic performance(yield) of the students in the academic semester 2007-1, in the subject of Thesis the lllrd of the Faculty(Power) of Education and Humanidades-Rioja of San's Martin National University-Tarapoto. The sample was constituted by 20 students of the subject of Thesis the lllrd belonging to the X cycle of the professional careers(races) of the initial level, primary and secondary, in the academic semester 2007-1. Gathered the information of this sample and accused by means of her(it) t - student, where tc:-2,87 it(he,she) falls down in the region of rejection, being tt:-2, 101. Since(as,like) te E RR, has allowed to reject the void hypothesis and to accept the alternate one, in consequence, is confirmed that the attitudes towards the scientific investigation(research) it(he,she) relates directly proportionally to the academic performance(yield) of the students in the academic semester 2007-I, in the subject of Thesis the lllrd of the Faculty(Power) of Education and Humanidades-Rioja of San's Martin National University-Tarapoto